Cross‐species comparison of behavioral neurodevelopmental milestones in the common marmoset monkey and human child. Issue 7 (1st August 2017) - Ausderau, Karla K.; Dammann, Caitlin; McManus, Kathy; Schneider, Mary; Emborg, Marina E.; Schultz‐Darken, Nancy
Abstract: The common marmoset ( Callithrix jacchus ) is an increasingly popular non‐human primate species for developing transgenic and genomic edited models of neurological disorders. These models present an opportunity to assess from birth the impact of genetic mutations and to identify candidate predictive biomarkers of early disease onset. In order to apply findings from marmosets to humans, a cross‐species comparison of typical development is essential. Aiming to identify similarities, differences, and gaps in knowledge of neurodevelopment, we evaluated peer‐reviewed literature focused on the first 6 months of life of marmosets and compared to humans. Five major developmental constructs, including reflexes and reactions, motor, feeding, self‐help, and social, were compared. Numerous similarities were identified in the developmental sequences with differences often influenced by the purpose of the behavior, specifically for marmoset survival. The lack of detailed knowledge of marmoset development was exposed as related to the vast resources for humans.